A REVIEW OF EXPERT SYSTEMS IN LIBRARY AND INFORMATION SCIENCE - De Silva, Sharon Manel (Malaysian Journal of Library and Information Science, 1997)
Reviews 422 published sources on expert system (ES) applications in library and information science (LIS) domains. The literature was reviewed under five categories which described ES applications in;LIS (general); technical services which include cataloguing and classification; public services which include reference services, information search and retrieval and document delivery; abstracting and indexing and; acquisition and collection development.